TWO NEW SPECIES OF Galeopsomyia (HYMENOPTERA, EULOPHIDAE) FROM BRAZIL - Perioto, Nelson Wanderley; Costa, Valmir Antonio; Lara, RogÃ©ria InÃªs Rosa (REVISTA DE AGRICULTURA, 2015)
TWO NEW SPECIES OF Galeopsomyia (HYMENOPTERA, EULOPHIDAE) FROM BRAZIL